Erratum to: Collective Recognition and Regional Parliaments: Navigating Statehood Conflict(Global Studies Quarterly (2021) 1:3 (ksab011) DOI: 10.1093/isagsq/ksab011) - Kyris, George; Luciano, Bruno [UNESP] (Oxford University Press (OUP), 2023)
In the originally published version of this manuscript, the supplementary material was inadvertently omitted. This error has been corrected.